Development of a Novel Nanocomposite Based on Reduced Graphene Oxide/Chitosan/Au/ZnO and Electrochemical Sensor for Determination of Losartan - Ghanbari, Khadijeh; Sivandi, Ashraf (Current Analytical Chemistry, 2020)
Background: Hypertension is a major risk for morbidity and mortality, while hypertension is associated with cardiovascular disease and organ damage. Recent research efforts have focused on the development of highly selective angiotensin receptor blockers. In which losartan (LOS) is considered as a new generation of an effective oral drug product against arterial hypertension. Therefore, the determination of drugs in biological fluids, pharmaceuticals (tablets), and wastewater is of critical importance for clinical applications, forensics, quality control, and environmental protection that call for the development of analytical methods. Many ranges of methods such as spectroscopic methods and chromatographic techniques have been developed to determine LOS in pharmaceutical formulations and biological fluids. However, there are crucial interference problems in these methods. For these reasons, more sensitive, desirable, portable, low-cost, simple, and selective nanocomposite-based sensors are needed in terms of health safety. Nanomaterials such as reduced graphene oxide, chitosan, and metal nanoparticles are used to improve the sensitivity in the development of electrochemical sensors. Objective: In this study, a novel reduced graphene oxide (RGO), chitosan (Chit), gold (Au), and zinc oxide (ZnO) nanocomposite (RGO/Chitosan/Au/ZnO) was synthesized and used to develop a sensitive and efficient electrochemical sensor for LOS detection. Methods: Modification of electrode by RGO/Chit/Au/ZnO nanocomposite was performed in four stages with GO (at -2.0 V for 150 s), Chitosan (at -3.0 V for 300 s), Au nanoparticles (at -0.4 V for 400 s), and Zn nanoflowers like (at -0.7 V for 1200 s). The RGO/Chitosan/Au/ZnO nanocomposite was characterized by field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR). Cyclic Voltammetry (CV) and Differential Pulse Voltammetry (DPV) were used to detect LOS, and the influence of pH value, scan rate, accumulation potential, and time also losartan concentration on the performance of ZnO/Au/Chitosan/RGO/GCE were investigated. In order to investigate the selectivity of the modified electrode for the determination of LOS, the effect of possible interfering species was evaluated and showed that these species are not interferences. Also, the reproducibility of the modified electrode was investigated and implying that the RGO/Chit/Au/ZnO nanocomposite was highly reproducible. Results: The modified electrode was used as a sensor for the selective and sensitive determination of LOS with a detection limit of 0.073 μM over the dynamic linear range of 0.5μM to 18.0 μM. In addition, electrochemical oxidation of LOS was well recovered in pharmaceutical formulations. Conclusion: LOS is used to treat high blood pressure, taking into account the oxidation of this compound, the use of electrochemical based sensors, ideally suited to a specific chemical species, can be fully selectable and High-sensitivity answer is very important. In this study, the electrodes with RGO/Chit/Au/ZnO nanocomposite were modified by the electrochemical method. Nanocomposites were characterized by various methods such as FE-SEM, FT-IR, XRD, Raman, and XPS. The electrocatalytic activity of the modified electrode was then investigated for measuring LOS. According to the results of the modified electrode, high sensitivity, reproducibility, and selectivity have been shown to oxidize this composition.
Keywords: electrochemical sensor